Recent Advance in Tumor Microenvironment-Based Stimuli-Responsive Nanoscale Drug Delivery and Imaging Platform - Cui, Fengzhi; Liu, Jianhua; Pang, Siwen; Li, Bo (Frontiers in Pharmacology, 2022)
The tumor microenvironment (TME) plays an important role in the development, progression, and metastasis of cancer, and the extremely crucial feature is hypoxic and acidic. Cancer-associated fibroblasts (CAFs), extracellular matrix (ECM), mesenchymal cells, blood vessels, and interstitial fluid are widely recognized as fundamentally crucial hallmarks for TME. As nanotechnology briskly boomed, the nanoscale drug delivery and imaging platform (NDDIP) emerged and has attracted intensive attention. Based on main characteristics of TME, NDDIP can be classified into pH-sensitive delivery and imaging platforms, enzyme-sensitive delivery and imaging platforms, thermo-sensitive delivery and imaging platforms, redox-sensitive delivery and imaging platforms, and light-sensitive delivery and imaging platforms. Furthermore, imageology is one of the significant procedures for disease detection, image-guided drug delivery, and efficacy assessment, including magnetic resonance imaging (MRI), computed tomography (CT), ultrasound (US), and fluorescence imaging. Therefore, the stimuli-responsive NDDIP will be a versatile and practicable tumor disease diagnostic procedure and efficacy evaluation tool. In this review article, we mainly introduce the characteristics of TME and summarize the progress of multitudinous NDDIP as well as their applications.